Lethal and sub lethal effects of a synthetic detergent on liver, muscle and branchial Na+ K+ ATPase enzyme activity in Labeo rohita - Chellan, Bijoy; Ramesh, M; Ramanujam, R Manavala (Indian Journal of Fisheries, 2011)
Synthetic detergents are a diverse group of compounds and part of a larger group known as surface-active agents or surfactants. In recent years there has been a rapid increase in the production of synthetic detergents which are used in industries and house hold purposes. These have become one of the important contributory substances that create pollution in natural water systems. Toxicological impacts of synthetic detergents have been well documented by many workers (Henderson et al., 1959; Abel,1974; Verma and Mohan,1976). A packetof commercial detergent usually contains 20% of active detergent, most commonly linear alkyl benzene sulphonate and an equal amount of sodium sulphate to make up the bulk of the powders, other ingredients are: inorganic phosphates,flourescers, foaming agents etc. Surface-active agents have been found in lakes, ponds and rivers polluted by wastes from industry and municipal sewage treatment plants.